The Issues of Teaching English in Elementary School Based on Students Engagement: Exploring Teachers’ Perspective - Zulfikar Noor; Farida Repelita Waty Kembaren (Scope : Journal of English Language Teaching, 2023)
The English-teaching problem is a significant issue that has been discussed in various contexts around the world, including English teachers’ issues, students’ assessments, curricula and textbooks, and the various variables that contribute to effective English as a foreign language (EFL) teaching. As a result, the purpose of the study is to explore 10 participants' perspectives on issues of teaching English in ELT classrooms. The purpose of this descriptive qualitative study is to investigate how teachers perceived the English teaching issue in relation to the students involved. Data were collected using an interview that included a single primary question about teaching English. Then, the data was analyzed by using content analysis. This study came to three major conclusions: (1) Learner motivation issues, (2) A problem with attitude, (3) An issue with the support system. Finally, problems with teaching English should not be underestimated because they have a significant impact on how well teachers teach the language in elementary schools. Teachers must be aware of their shortcomings in order to continually improve their teaching skills without becoming complacent.